Robotics For The Development of Preschool Children’s Creativity - Nurjanah, Novita Eka; Choirunnisa (Jurnal Smart Paud, 2023)
The use of technology in 21st century education is not unfamiliar. One form of technological innovation in the field of education is robotics. The use of robots in learning is in line with STEM learning, because children are invited to build their own desired robots, design their own robots, and enter coding according to their wishes so that this activity can stimulate children's creativity. This study aims to determine the application of robotics in the development of early childhood creativity. The research method used is systematic literature review. Literature sources come from international articles relevant to the topic of study from 2011 to 2021. The results show that robotics applied in early childhood learning can develop creativity. Educational robots can be used as a place for children to develop, apply, and channel ideas, thoughts, ideas, and creativity in a work. Robotic activities can introduce children to STEM or STEAM concepts as well as computational thingking so that in addition to creativity, children are trained in logical, creative, and structured thinking skills.